2013
DOI: 10.5488/cmp.16.13801
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio calculations for the structural properties of Zr-Nb alloys

Abstract: Ab-initio calculations for the structural properties of Zr-Nb alloys at different values of the niobium concentration are done at zero temperature. Different cases for Zr-Nb alloys with unit cells having BCC and HCP structures are considered. Optimal values of the lattice constants are obtained. Critical value for the niobium concentration corresponding to the structural transformation HCP → BCC at zero temperature is determined. Electronic densities of states for two different structures with niobium concentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Zr and its alloys are indeed widely used as cladding materials in nuclear reactors. 25 At room temperature, Zr takes the hexagonal closed packed (HCP) phase and transitions into a body centered cubic (BCC) phase at higher temperature, which is dynamically unstable at 0 K. 6 Since phase stability is usually required to prevent structural failures in nuclear applications, understanding the temperature dependent vibrational dynamics of elemental Zr is critical. Recently, Zong et al successfully reproduced the phase diagram of Zr using a potential developed by kernel ridge regression algorithm, 26 indicating that ML could be a promising tool to model lattice dynamics of dynamically unstable crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Zr and its alloys are indeed widely used as cladding materials in nuclear reactors. 25 At room temperature, Zr takes the hexagonal closed packed (HCP) phase and transitions into a body centered cubic (BCC) phase at higher temperature, which is dynamically unstable at 0 K. 6 Since phase stability is usually required to prevent structural failures in nuclear applications, understanding the temperature dependent vibrational dynamics of elemental Zr is critical. Recently, Zong et al successfully reproduced the phase diagram of Zr using a potential developed by kernel ridge regression algorithm, 26 indicating that ML could be a promising tool to model lattice dynamics of dynamically unstable crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of the lattice parameter, a Zr , for β Zr-Nb alloys versus niobium concentration was previously evaluated in Ref. [25]. The authors have shown that with an increase in the niobium concentration the lattice constant decreases according to the linear law.…”
Section: Structure Optimizationmentioning
confidence: 99%
“…For example: the elastic moduli of Zr single crystal and their temperature dependence were experimentally studied early in 1964 by Fisher and coworker [10]; the elastic constants of Nb single crystal were experimentally studied at 27 • C by Bolef [11]; the elastic constants of Nb-rich alloys Nb-xZr with bcc structure from 4.2 • K up to room temperature were experimentally determined by Hayes and coworker [12] in 1973; and also from zero temperature to the melting point were studied both experimentally and theoretically by Ashkenazi and coworkers [13] in 1978. Varshni [14]; Fast, et al [15]; and Olsson [16] have investigated the temperature dependence of elastic constants of zirconium; Peng, et al have studied the pressure effect on stabilities of self-interstitials in hcp-zirconium using first-principles method [17]; Liu, et al [18]; Wang, et al [19]; have calculated the elastic constants of niobium at normal pressure and high pressures, respectively; Kharchenko, et al have investigated [20] the effect of Nb concentration on the lattice constants of Zr-xNb; Wang, et al [21]; Weck, et al [22]; Al-Zoubi, et al [23]; have investigated the elastic constants for Zr-Nb alloys; Xin, et al have studied the point defect properties (such as formation energies) in hcp and bcc Zr with trace solute Nb by ab initio calculations [24]. However, to our knowledge, the mechanical properties of Zr-xNb alloys in presence of defects have not been thoroughly investigated, which will be studied in the present work.…”
Section: Introductionmentioning
confidence: 99%